PROVERBS AND APHORISMS IN ABAY'S WORDS OF EDIFICATION AND MODERN SPIRITUAL VALUES (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article examines the use of folk proverbs and aphorisms in The Book of Words of the great Kazakh figure Abai Kunanbayev, based on his value system. The proverbs and aphorisms used by Abai reflect the fundamental value orientations of the Kazakh people. Particular attention is paid to proverbs and sayings that reflect our spiritual values ​​in Abai's proverbs, which were criticized by the poet. The variable idiomatic meanings, emotional and expressive coloring, and social significance of proverbs sharply criticized in Abai's sayings are considered and formulated in unity with Abai's thoughts. The article determines the place of proverbs and aphorisms, to which Abai, the great educator of our people, paid special attention, in the system of spiritual values ​​of the modern era.Currently, in the minds of young people, instead of socially significant values, individual behavioral traits are increasingly manifesting, and contradictory worldviews are becoming increasingly evident. Digital transformations of globalization are shaping the development of social values, leading to the emergence and consolidation of new values, and changes in behavioral strategies. These transformations make it particularly important to predict these changes in thinking, their mechanisms of action and direction, as well as prevent negative behaviors, taking into account the evolving situation.This article analyzes the role of proverbs and aphorisms, particularly prominent in Abai's The Book of Words, as a means of communication and education, and concludes that corrective interventions are necessary to foster basic positive values ​​in young people.